Pemanfaatan Tumbuhan Pangan oleh Suku Dayak Kanayatn di Kecamatan Ngabang Kabupaten Landak - Mukarlina,, Nurhajijah, Riza Linda, (Universitas Tanjungpura, 2017)
Landak regency has potensial natural resources as food sources. The research work aimed to find out types of food planst, food processing, and parts of food planst consumed by Dayak Kanayatn in Pak Mayam village, Ngabang district, Landak regency. The study was conducted from July to September 2016 in Pak Mayam village and Biologi laboratory of Mathematics and Natural Science faculty of Universitas Tanjungpura Pontianak. The research work employed purposive sampling methodology. The result of the research suggested that there are 43 kinds of plants of 26 families consumed as food. The most plant family consumed are Poaceae and Myrtaceae by 9,3%. Part of plants that is eaten is the fruit by 58%. The use of plants consists of five 5 categories; namely vegetables, fruits, spices, root vegetables, and cereal grain. Food plands are prepared without processing by being eaten directly and with processing by boiling, frying, smashing, stir frying, and baking them.